2006
DOI: 10.1682/jrrd.2005.03.0058
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a 6-week arm exercise program on walking ability and health status after hip arthroplasty: A 1-year follow-up pilot study

Abstract: Abstract-The influence of an upper-limb interval-training program after total hip arthroplasty (THA) in elderly patients was studied during a 1 yr follow-up on health status and walking ability. After surgery, 14 patients were randomly assigned to the control group that started a 6 wk general rehabilitation program or the training group that combined it with an interval exercise program on an arm ergometer. A Western Ontario and McMaster Universities (WOMAC) Osteoarthritis Index was completed 1 mo before and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 17 publications
(22 reference statements)
1
31
0
4
Order By: Relevance
“…By 12 weeks, the mean walking distance of participants was 400.4 (SD = 116.6) meters, which is equivalent to the distance a healthy older adult walks in 6 minutes (Gremeaux et al, 2008). These results are comparable with the findings of Maire et al (2006), who identified a 6-minute walking distance of 405 (range = 270Y508) meters in the upper-limb-interval training group compared with 259 (range = 218Y302) meters in the control group after 2 months of study. After 12 weeks of training, the WOMAC score of participants decreased by 78.94%, with a mean change of 39.10 (p G .001).…”
Section: Discussionsupporting
confidence: 78%
“…By 12 weeks, the mean walking distance of participants was 400.4 (SD = 116.6) meters, which is equivalent to the distance a healthy older adult walks in 6 minutes (Gremeaux et al, 2008). These results are comparable with the findings of Maire et al (2006), who identified a 6-minute walking distance of 405 (range = 270Y508) meters in the upper-limb-interval training group compared with 259 (range = 218Y302) meters in the control group after 2 months of study. After 12 weeks of training, the WOMAC score of participants decreased by 78.94%, with a mean change of 39.10 (p G .001).…”
Section: Discussionsupporting
confidence: 78%
“…In addition, it has been shown that arm crank exercise improves health status and physiological well-being in several populations (Hicks et al, 2003;Grange et al, 2004;Maire et al, 2004;Zwierska et al, 2005;Maire et al, 2006;Verney et al, 2006;Mendelsohn et al, 2008). The arm crank _ VO 2peak was about 58% of treadmill _ VO 2peak .…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that ACE is a valid means for predicting _ VO 2max and may be a useful alternative for the Bruce treadmill test in people unable to perform lower body ergometry. In addition, it has been shown that arm crank exercise improves health status and physiological well-being in several populations (Hicks et al, 2003;Grange et al, 2004;Maire et al, 2004;Zwierska et al, 2005;Maire et al, 2006;Verney et al, 2006;Mendelsohn et al, 2008). Although the effect of ACE has not yet been determined in a number of populations where it may ultimately prove useful in reducing mortality and morbidity, therefore, further research is necessary surrounding this topic.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies in HR MAX for the arms provide significant relevance for older and clinical populations. For example, in some clinical settings where upper body exercise training is popular, such as those undergoing hip replacement rehabilitation (Maire et al 2006), exercise is terminated when individuals achieve a percentage of HR MAX (e.g. 85% HR MAX ), which would result in a more severe exercise intensity when performed with the arms.…”
Section: Discussionmentioning
confidence: 99%